49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3678
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Reducing Sonic Boom Strength by Tailoring the Shape of the Propulsive Streamtube

Abstract: Over the past decade, Gulfstream Aerospace Corporation has published on several methods for tailoring the shape of the nacelle for reducing its profile and contribution to the sonic boom signature of an aircraft traveling at supersonic speed. Through computational and experimental campaigns, these design methods have been shown effective at reducing the strength of the nacelle's compression features. However, even heavily attenuated shocks can remain unacceptably strong for aircraft constrained by an ultra-qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Only the minimum-bound geometric constraints prevent the spike from disappearing completely. This spike geometry is very similar to the design presented by Conners et al 1 Thrust is reduced by 2.7% compared to the benchmark case. Furthermore, the shocks emanating from the nozzle lip region are stronger than those in the first design problem, perhaps so much so that they could affect the ground pressure signature despite airframe shielding.…”
Section: Supersonic Nozzle Shape Optimizationsupporting
confidence: 72%
See 2 more Smart Citations
“…Only the minimum-bound geometric constraints prevent the spike from disappearing completely. This spike geometry is very similar to the design presented by Conners et al 1 Thrust is reduced by 2.7% compared to the benchmark case. Furthermore, the shocks emanating from the nozzle lip region are stronger than those in the first design problem, perhaps so much so that they could affect the ground pressure signature despite airframe shielding.…”
Section: Supersonic Nozzle Shape Optimizationsupporting
confidence: 72%
“…We consider a notional shrouded supersonic nozzle design to demonstrate shape optimization with mass-flowrate constraints and multiple inflow boundaries. This case is roughly based on the high-flow bypass nacelle design presented by Conners et al 1 and studied by Heath et al 38 to minimize nacelle effects on sonic-boom noise. Figure 16 shows the baseline geometry, which consists of a traditional axisymmetric spike nozzle that is mounted inside a shroud.…”
Section: Supersonic Nozzle Shape Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, conceptual design often omits viscous aerodynamic effects which can have a detrimental impact on installed propulsive performance and vehicle sonic boom loudness levels. For example, prior research [5][6][7] has indicated that adding viscous or propulsion effects into a pre-optimized low-boom airframe signature can greatly compromise sonic boom performance.…”
Section: Introductionmentioning
confidence: 99%